2008
DOI: 10.1016/j.annemergmed.2007.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention for Hazardous and Harmful Drinkers in the Emergency Department

Abstract: Study Objective-To determine efficacy of emergency practitioner performed brief intervention for hazardous/harmful drinkers in reducing alcohol consumption and negative consequences in an Emergency Department (ED) setting.Methods-A randomized clinical trial (Project ED Health) was conducted in an urban ED from 5/2002 to 11/2003 for hazardous/harmful drinkers. Patients ≥ 18 who screened above National Institute for Alcohol Abuse and Alcoholism guidelines for "low risk" drinking or presented with an injury in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(159 citation statements)
references
References 29 publications
7
150
1
1
Order By: Relevance
“…The SIP is a 15-item questionnaire that assesses, over the past 3 months, the presence of alcohol-related consequences in various dimensions: physical, interpersonal, intrapersonal, impulse control and social responsibility. 10,[25][26][27] . The course of unhealthy alcohol use tends to involve self-change with or without formal help, with a substantial proportion of individuals either abstaining or drinking moderate amounts without consequences a year later.…”
Section: Discussionmentioning
confidence: 99%
“…The SIP is a 15-item questionnaire that assesses, over the past 3 months, the presence of alcohol-related consequences in various dimensions: physical, interpersonal, intrapersonal, impulse control and social responsibility. 10,[25][26][27] . The course of unhealthy alcohol use tends to involve self-change with or without formal help, with a substantial proportion of individuals either abstaining or drinking moderate amounts without consequences a year later.…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences in consumption, but three studies (with 785 people) found differences in recurrent injury. 33 Another highquality randomized controlled trial by D'Onofrio et al 9 (88% enrollment and 92% 12-month follow-up) showed no differences in consumption measures.…”
Section: What Do We Know About Sbi?mentioning
confidence: 99%
“…Project ASSERT was next established in 1999 at the Yale-New Haven Hospital ED. 7 Both programs are current line items in their hospital budgets, provide reimbursable services, and have led to NIH-funded research trials of motivational interviewing 8,9 and training curricula. 10,11 A 14-site Academic ED SBIRT Research Collaborative trained 402 ED nurses, nurse practitioners, residents, faculty, social workers, and physician assistants who intervened with at-risk and dependent drinkers, with resulting declines in consumption and a parallel increase in the number of persons drinking within the NIAAA's low-risk guidelines.…”
Section: Ed Sbirt Knowledge Translation Highway From Research To Clinmentioning
confidence: 99%
“…Several studies suggest that it is the optimal instrument for medical settings, 69,[73][74][75] but this is not without controversy in the literature. 69,76,77 Although there are a variety of efficacious screening instruments, 39,42,56,78,79 their effectiveness when implemented in the clinical setting varies, not only in light of their test characteristics, but also because of factors such as ease of administration in routine clinical care. For example, the AUDIT is long and needs to be scored.…”
Section: Recommendation 1: Screeningmentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42] Several studies demonstrated a beneficial effect on negative consequences. 35,38,42,43 While the Academic SBIRT trial, using a quasi-experimental methodology, found reduced consumption at 3 months, 12 effects on decreasing alcohol consumption have not been consistent in other studies. 35 Further confounding interpretation of the evidence is that the published studies include a wide variety of patient populations: some only young adults, 44 many only with injured patients.…”
Section: Alcoholmentioning
confidence: 99%